KONSELING MULTIMODAL UNTUK MENGATASI STRES PADA ORANG DEWASA - Rina Nurhudi Ramdhani; Yessika Nurmasari (Journal of Innovative Counseling : Theory, Practice, and Research, 2017)
Multimodal counseling aims to help counselees solve the problem with the right technique which is based on the human dimension of the dominant modality. This approach views the individual has a threshold of tolerance of frustration, stress, pain, noise, cold, and different pollution. Counseling process considered success when counselees be able to identify the impact of the stress experienced by analysis of BASIC ID; managing emotions; and be able to make plans of action when the incident/ event stressors occur. Adulthood should have a balance career achievement, but in this era of globalization, many adulthood have career imbalance that cause problems. Multimodal counseling is suitable for coping strees of career development in middle adulthood.